Response of Plant-Colonizing Pseudomonads to Hydrogen Peroxide - Katsuwon, J. (1989)
Colonization of plant root surfaces by Pseudomonas putida may require mechanisms that protect this bacterium against superoxide anion and hydrogen peroxide produced by the root. Catalase and superoxide dismutase may be important in this bacterial defense system. Stationary-phase cells of P. putida were not killed by hydrogen peroxide (H(2)O(2)) at concentrations up to 10 mM, and extracts from these cells possessed three isozymic bands (A, B, and C) of catalase activity in native polyacrylamide gel electrophoresis. Logarithmic-phase cells exposed directly to hydrogen peroxide concentrations above 1 mM were killed. Extracts of logarithmic-phase cells displayed only band A catalase activity. Protection against 5 mM H(2)O(2) was apparent after previous exposure of the logarithmic-phase cells to nonlethal concentrations (30 to 300 μM) of H(2)O(2). Extracts of these protected cells possessed enhanced catalase activity of band A and small amounts of bands B and C. A single form of superoxide dismutase and isoforms of catalase were apparent in extracts from a foliar intercellular pathogen, Pseudomonas syringae pv. phaseolicola. The mobilities of these P. syringae enzymes were distinct from those of enzymes in P. putida extracts.